Integrasi Sharepoint Portal dan Office Web Application untuk Mendukung Layanan Cloud - Kridalukmana, Rinta; Martono, Kurniawan Teguh (Jurnal Sistem Komputer, 2014)
Abstract – Nowadays, information technology has been entering new era of cloud computing, whereas internet user can save and manipulate their file using the cloud. For more, not only provides storage and manipulation function, cloud can be used for document approval between employee to their manager. One of many solution to accommodate the needs mentioned above is sharepoint application by Microsoft. Web application maintained by sharepoint can be used as user interface to collaborate between users. To support document sharing and manipulation, sharepoint can be integrated with Office Web Application (OWA). By using OWA, user will meet experience using Microsoft Office through web browser. Considering Microsoft Office used by most people, the integration between sharepoint as web application farm and Office Web Application can be an altertative to enter cloud computing era